2018
DOI: 10.7326/m17-0996
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Racial/Ethnic and Nativity Disparities in Cardiovascular Health Among Adults Without Prevalent Cardiovascular Disease in the United States, 1988 to 2014

Abstract: National Institute of Neurological Disorders and Stroke and National Center for Advancing Translational Sciences of the National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 55 publications
2
60
1
Order By: Relevance
“…Recent analyses of National Health and Nutrition Examination Survey (NHANES) data show persistent CV health disparities by LS7 composite scores between whites and AAs and call for multifaceted, community-level interventions to curtail and eradicate these gaps. 6 Our intervention, although a research prototype, offers an innovative medium to engage AA patients beyond office-based encounters through mobile technology with an overarching goal of diminishing CV disease risk and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses of National Health and Nutrition Examination Survey (NHANES) data show persistent CV health disparities by LS7 composite scores between whites and AAs and call for multifaceted, community-level interventions to curtail and eradicate these gaps. 6 Our intervention, although a research prototype, offers an innovative medium to engage AA patients beyond office-based encounters through mobile technology with an overarching goal of diminishing CV disease risk and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted for baseline age (years, continuous), sex, and race/ethnicity (non-Hispanic white, non-Hispanic black, Mexican American, and others) in model 1. We further adjusted for education level (less than high school, high school or equivalent, and college or above), family income-poverty ratio level (0-1.0, 1.1-3.0, >3.0),26 marital status (married, separated including widowed and divorced groups, and never married), smoking status (never, former, and current smoker), drinking status (non-drinker, low to moderate drinker defined as drinking <1 drink/day in women and <2 drinks/day in men, and heavy drinker defined as ≥1 drink/day in women and ≥2 drinks/day in men),27 and family history of diabetes or heart attack in model 2. We additionally adjusted for baseline moderate to vigorous leisure time physical activity level (0, 1-2, or ≥3 times/week),28 dietary pattern represented by the healthy eating index scores (HEI-1995 for NHANES 1988-94 and HEI-2015 for NHANES 1999-2014, both in quarters),29 and self reported health status (very good to excellent, good, and poor to fair).…”
Section: Methodsmentioning
confidence: 99%
“…Brown et al found that the percentage of NHBs with optimal Life's Simple 7 scores (a measure that includes blood pressure, cholesterol, hemoglobin A 1c , body mass index, physical activity, diet, and smoking) was 22 and 8 percentage points less, relative to NHWs, ages 25-44 and ‡65, respectively. 2 There is evidence that self-employment is associated with improved cardiovascular health measures among the general population. For instance, Yoon et al found that self-employment was positively associated with physical exercise and normal weight when controlling for demographics, education, income, family structure, access to health care, occupation type, and census region.…”
Section: Introductionmentioning
confidence: 99%